Freshwater Biology - Freshwater Biology (Wiley, 2026)
Freshwater Biology is a freshwater ecology journal publishing innovative papers on the aquatic biology of freshwater environments. We welcome manuscripts that integrate experiments, laboratory and field research. We encourage studies from less well researched areas of the world. Our journal’s focus is freshwater ecology, including rivers, lakers, connected groundwaters, springs, floodplains, rockpools, streams, and wetlands. We publish studies of microbes, algae, macrophytes, invertebrates, vertebrates and those concerning whole systems and their related environmental aspects.
FI 0.84
Q2
Keywords: Life Sciences; Ecology & Organismal Biology; Acuerdos transformativos; Transformative agreements; Ecología de agua dulce; Biología acuática; Ecosistemas de agua dulce